2004
DOI: 10.1093/oxfordjournals.schbul.a007071
|View full text |Cite
|
Sign up to set email alerts
|

The Schizophrenia Patient Outcomes Research Team (PORT): Updated Treatment Recommendations 2003

Abstract: Since publication of the original Schizophrenia Patient Outcomes Research Team (PORT) treatment recommendations in 1998, considerable scientific advances have occurred in our knowledge about how to help persons with schizophrenia. Today an even stronger body of research supports the scientific basis of treatment. This evidence, taken in its entirety, points to the value of treatment approaches combining medications with psychosocial treatments, including psychological interventions, family interventions, suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
335
0
9

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 578 publications
(356 citation statements)
references
References 205 publications
(237 reference statements)
12
335
0
9
Order By: Relevance
“…Future intervention studies should incorporate QOL as an outcome measure to assess the effects of treatment on QOL. Mounting evidence suggests that psychosocial treatments (e.g., cognitive behavioral therapy, supported employment, social skills training, assertive community treatment, and cognitive training) are a necessary adjunct to antipsychotic medications (Granholm et al, 2005;Lehman et al, 2004;Twamley et al, 2003a;Twamley et al, 2003b). With aggressive use of adjunctive treatments to target depression and negative symptoms, QOL in schizophrenia may be improved.…”
Section: Discussionmentioning
confidence: 99%
“…Future intervention studies should incorporate QOL as an outcome measure to assess the effects of treatment on QOL. Mounting evidence suggests that psychosocial treatments (e.g., cognitive behavioral therapy, supported employment, social skills training, assertive community treatment, and cognitive training) are a necessary adjunct to antipsychotic medications (Granholm et al, 2005;Lehman et al, 2004;Twamley et al, 2003a;Twamley et al, 2003b). With aggressive use of adjunctive treatments to target depression and negative symptoms, QOL in schizophrenia may be improved.…”
Section: Discussionmentioning
confidence: 99%
“…They also received a brochure written in lay language that presents five schizophrenia treatment recommendations addressed by the Web-based tool, including maintenance dose of antipsychotic medication, prophylactic antiparkinson medication, antidepressant treatment, family intervention, and supported employment (7). The combination of brochure and video mirrored the information content of the Web-based intervention but without the personalized feedback or video clips role-modeling discussion of treatment issues provided online.…”
Section: Methodsmentioning
confidence: 99%
“…This study furthered this line of work by developing an Internet-based interactive computer tool to educate patients with schizophrenia about evidence-based treatment guidelines and to compare their care to guidelines and receive feedback (7). The design of the intervention was also motivated by a study that found disparities between the evidence-based treatment recommendations of the Schizophrenia Patient Outcomes Research Team, known as PORT, and the services received by persons with schizophrenia (8,9).…”
mentioning
confidence: 99%
“…We hypothesize this is due to the fact that largely accepted "first line" treatments for both of this conditions are medication rather than behavioral therapy, or medication in adjunct with behavioral therapy (although this is not the case for pre-school children diagnosed with ADHD due to the risks of stimulant medication in that age group) (American Academy of Pediatrics, 2011;Buchanan et al, 2009;Lehman, Kreyenbuhl et al, 2004;Lehman, Liebermanet al, 2004;Kutcher et al, 2004).…”
Section: Attention Deficit Hyperactivity Disorder (Adhd) and Schizophmentioning
confidence: 99%